ANALYSIS OF STUDENTS’ BUSINESS INDEPENDENCE AND ENTREPRENEURIAL RESILIENCE THROUGH THE USE OF DIGITAL TECHNOLOGY IN A BUSINESS STUDENT COMMUNITY - Jahju Hartanti; Wiwik Robiatul Adawiyah; Elia Firda Mufidah (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
The purpose of this study is to analyze the influence of business independence on students through the use of digital technology and entrepreneurial resilience. This research method uses correlational with a total population of 254 students who take part in the business student community. The number of samples in this study was 120 students with a sample taking technique using a probability sampling technique. Data analysis using path analysis techniques. The results of the analysis show that the use of digital technology and resilience affects business independence. The level of student business independence in the moderate category is 45%, while the student entrepreneurial resilience has a high category of 47%. The use of digital technology is needed to create product innovations to become independent prospective entrepreneurs. The recommendation based on the results of this study is the need for training provided to members of the business student community in improving business independence.